2021
DOI: 10.1021/acsomega.1c02255
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Symmetrically versus Unsymmetrically Proton-Bridged Hexa-Iron Clusters

Abstract: Syntheses and magnetic and structural characterization of hexa-iron complexes of derivatized salicylaldoximes are discussed. Complexation of Fe(BF 4 ) 2 ·6H 2 O with each ligand (H 2 L1 and H 4 L2 ) in a methanolic-pyridine solution resulted in hexa-iron compounds ( C1 and C2 , respectively), which each contain two near-parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…A combination of three transition metals and one lanthanide ion have, in the past, been used to template the macrocyclization of 2,3-dihydroxybenzene-1,4-dicarbaldehyde with various diamine linkers. The Plieger group have previous experience in preparing multinuclear metal complexes with potentially interesting magnetic properties, and the Ishida group have expertise in the magnetic characterization of 3d–4f complexes, particularly those involving copper­(II). Inspired by the Zn 3 La system first reported by Nabeshima et al and later extended to other metal combinations by Brooker et al, ,, we investigated the self-assembly and successful crystallization of L 3 Cu 3 Ln complexes using the acyclic ligand system 1,4-diformylnaphthalene-2,3-diol (H 2 L ). While there are numerous examples of magnetically coupled Cu–Ln systems, , throughout the literature, there are very few Cu 3 Ln complexes featuring four in-plane metal ions; and a CCDC search indicated that, outside of the previously mentioned complexes of Nabeshima and Brooker, there are no other structurally characterized examples which exclusively contain Cu–O–Ln bridges.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of three transition metals and one lanthanide ion have, in the past, been used to template the macrocyclization of 2,3-dihydroxybenzene-1,4-dicarbaldehyde with various diamine linkers. The Plieger group have previous experience in preparing multinuclear metal complexes with potentially interesting magnetic properties, and the Ishida group have expertise in the magnetic characterization of 3d–4f complexes, particularly those involving copper­(II). Inspired by the Zn 3 La system first reported by Nabeshima et al and later extended to other metal combinations by Brooker et al, ,, we investigated the self-assembly and successful crystallization of L 3 Cu 3 Ln complexes using the acyclic ligand system 1,4-diformylnaphthalene-2,3-diol (H 2 L ). While there are numerous examples of magnetically coupled Cu–Ln systems, , throughout the literature, there are very few Cu 3 Ln complexes featuring four in-plane metal ions; and a CCDC search indicated that, outside of the previously mentioned complexes of Nabeshima and Brooker, there are no other structurally characterized examples which exclusively contain Cu–O–Ln bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers still pay considerable attention to binuclear oxo-bridged non-haem iron complexes (containing the Fe–O–Fe unit) due to their potential uses in biological processes, catalysts, magnetic materials, etc. 1–8 We can design an appropriate ligand to chelate metal centers in a special frame and control the electron withdrawal from the metal ion core, thereby modifying the intramolecular exchange interaction. 9,10 Binuclear oxo-bridged complexes mainly contain tribridged-, 11 dibridged- 12,13 and monobridged- 14 species.…”
Section: Introductionmentioning
confidence: 99%